Couple to celebate 50th (Raton Range June 2, ?)
Newspaper Article on the 50th Anniversary of Sam and Mary Garcia.
Master list item #: 65
File location is in the Raton File Cabinet
Keywords: Garcia, Sam; Garcia, Mary; St. Patrick & St. Joseph's Parish; Spur Lounge; Local History; Biography; Life and Customs; Marriage; Celebration; Anniversary; Raton, New Mexico